Hexane Extracts of Calophyllum brasiliense Inhibit the Development of Gastric Preneoplasia in Helicobacter felis Infected INS-Gas Mice - Lemos, Larissa M. S.; Miyajima, Fabio; Castilho, Geovane R. C.; Martins, Domingos Tabajara O.; Pritchard, D. Mark; Burkitt, Michael D. (Frontiers in Pharmacology, 2017)
Objectives: Indigenous Latin American populations have used extracts from Calophyllum brasiliense, a native hardwood, to treat gastrointestinal symptoms for generations. The hexane extract of Calophyllum brasiliense stem bark (HECb) protects against ethanol-mediated gastric ulceration in Swiss-Webster mice. We investigated whether HECb inhibits the development of gastric epithelial pathology following Helicobacter felis infection of INS-Gas mice. Methods: Groups of 5 male, 6-week-old INS-Gas mice were colonised with H. felis by gavage. From 2 weeks after colonisation their drinking water was supplemented with 2% Tween20 (vehicle), low dose HECb (33 mg/L, lHECb) or high dose HECb (133 mg/L, hHECb). Equivalent uninfected groups were studied. Animals were culled 6 weeks after H. felis colonisation. Preneoplastic pathology was quantified using established histological criteria. Gastric epithelial cell turnover was quantified by immunohistochemistry for Ki67 and active-caspase 3. Cytokines were quantified using an electrochemiluminescence assay. Results: Vehicle-treated H. felis infected mice exhibited higher gastric atrophy scores than similarly treated uninfected mice (mean atrophy score 5.6 ± 0.87 SEM vs 2.2 ± 0.58, p<.01). The same pattern was observed following lHECb. Following hHECb treatment, H. felis status did not significantly alter atrophy scores. Gastric epithelial apoptosis was not altered by H. felis or HECb administration. Amongst vehicle-treated mice, gastric epithelial cell proliferation was increased 2.8 fold in infected compared to uninfected animals (p<.01). Administration of either lHECb or hHECb reduced proliferation in infected mice to levels similar to uninfected mice. A Th17 polarised response to H. felis infection was observed in all infected groups. hHECb attenuated IFN-γ, IL-6 and TNF production following H.felis infection (70% (p<.01), 67% (p<.01) and 41 % (p<.05) reduction vs vehicle respectively). Conclusions: HECb modulates gastric epithelial pathology following H. felis infection of INS-Gas mice. Further studies are indicated to confirm the mechanisms underlying these observations.